Application of an independent parallel reactions model on the annealing kinetics of BEPO irradiated graphite - Lasithiotakis, M; Marsden, B; Marrow, T (2012)
Stored energy release rates have been determined for neutron irradiated graphite samples machined from an early air-cooled nuclear reactor (British Experimental Pile Zero or BEPO). The rate of release of stored energy was measured for both isothermal and linear rise heating rate differential scanning calorimetry experiments. The rate of release data were analysed using a thermal kinetics, independent parallel reactions model. The effect of annealing on the graphite crystalline structure was evaluated by investigating changes to X-ray diffraction spectra. A correlation between the calculated crystallite size and stored energy release is presented. A method for calculating the kinetic parameters for the annealing reaction is proposed and tested against the data. The method shows excellent consistency for both the isothermal and linear heating rate experiments (with less than 3% standard deviation). © 2012 Elsevier B.V. All rights reserved.